1984
DOI: 10.1080/00022470.1984.10465793
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Reaction of SO2with NaHCO3and Na2CO3

Abstract: The results are presented of a study conducted to examine the reactivity of NaHCO 3 and its thermally decomposed product, Na 2 CO 3 , with SO 2 as a function of temperature and particle size in a simulated flue gas. The NaHCO 3 reaction was found to be significantly more efficient than the Na 2 CO 3 reaction for temperatures less than 450°F (230°C) with a maximum efficiency of conversion occurring between 250 and 350°F. In the temperature range of 450-650°F, both compounds were observed to behave similarly. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 1 publication
2
25
0
Order By: Relevance
“…It shows that the reaction is somewhat slower at 130°C than at 160°C, while a reduction of the temperature to 110°C slows the reaction down substantially. Similar results are also available in the literature (Keener and Davis, 1984). In a pilot system with an electrostatic precipitator instead of the fabric filter, an ETA tot of approximately 50% has been reported at a stoichiometric ratio of 1.0 and a gas temperature of 200°C (Pilat and Wilder, 2007).…”
Section: Resultssupporting
confidence: 77%
“…It shows that the reaction is somewhat slower at 130°C than at 160°C, while a reduction of the temperature to 110°C slows the reaction down substantially. Similar results are also available in the literature (Keener and Davis, 1984). In a pilot system with an electrostatic precipitator instead of the fabric filter, an ETA tot of approximately 50% has been reported at a stoichiometric ratio of 1.0 and a gas temperature of 200°C (Pilat and Wilder, 2007).…”
Section: Resultssupporting
confidence: 77%
“…The effects of temperature, particle diameter, and pollutant concentration on SO 2 sorption by dry sorbents have been investigated using bench-scale fixedbed reactors. Keener and Davis (1984) found NaHC0 3 undergoing simultaneous decomposition and reaction with SO2 to be most reactive in the 250 to 350° F range with decreasing rate of reaction at higher temperatures. 8 Using a thermal gravimetric apparatus, Kimura and Smith (1987) reported similar results.…”
Section: Review Of Literaturementioning
confidence: 99%
“…10 Keener and Davis found that SO2 sorption by simultaneously decomposing NaHCO3 had at most a weak dependence on particle diameter. 8 Pollutant concentration also influences the sorption of SO2 by dry sorbents. Stern found that the rate of reaction (mass SO 2 sorbed per mass sorbent per time) of SO2 with predecomposed nahcolite at 500° F was directly proportional to SO 2 concentration.…”
Section: Dry Sorption Of Somentioning
confidence: 99%
“…For the same temperature used and contact times of the sorbent with gases containing SO 2 , sodium bicarbonate has a few times higher conversion rate 4 . The reaction of sodium bicarbonate with SO 2 can be described by the equation 5 : 2NaHCO 3(s) + SO 2(g) + x ½ O 2(g) → (1-x) Na 2 SO 3(s) + x Na 2 SO 4(s) + 2CO 2(g) + H 2 O (g) (1) In the literature a several models of this process are described.…”
mentioning
confidence: 99%
“…2NaHCO 3 → Na 2 CO 3 + H 2 O(g) + CO 2 (g) (3) Na 2 CO 3 + SO 2 → Na 2 SO 3 + CO 2 (4) The overall conversion of Na 2 SO 3 to NaHCO 3 is the sum of the partial conversions obtained for the established reaction path. The product, sodium sulfi te, which, in contact with oxygen from fl ue gas, forms sodium sulfate according to the reaction: Na 2 SO 3 + ½ O 2 → Na 2 SO 4 (5) Unauthenticated Download Date | 5/12/18 12:09 PM mill, fi ne impact mill and electromagnetic mill, differing in grinding technique. The 100 AFG fl uid bed mill from Hosokawa-Alpine was used for opposed jet milling, where the energy required to mill the material is passed through the intersecting streams of compressed air.…”
mentioning
confidence: 99%